2016
DOI: 10.1120/jacmp.v17i5.6338
|View full text |Cite
|
Sign up to set email alerts
|

Difference in dose‐volumetric data between the analytical anisotropic algorithm, the dose‐to‐medium, and the dose‐to‐water reporting modes of the Acuros XB for lung stereotactic body radiation therapy

Abstract: The purpose of this study was to evaluate the difference in dose‐volumetric data between the analytical anisotropic algorithms (AAA) and the two dose reporting modes of the Acuros XB, namely, the dose to water (AXB−normalDw) and dose to medium (AXB−normalDm) in lung stereotactic body radiotherapy (SBRT). Thirty‐eight plans were generated using the AXB−normalDm in Eclipse Treatment Planning System (TPS) and then recalculated with the AXB−normalDw and AAA, using identical beam setup. A dose of 50 Gy in 4 fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The effect of specifying the dose to medium should be further investigated. Although a study of Mampuya et al showed that dose to medium produced higher values than dose to water, the differences in PTV D95% were small and range between 0 and 0.7% [17].…”
Section: Discussionmentioning
confidence: 90%
“…The effect of specifying the dose to medium should be further investigated. Although a study of Mampuya et al showed that dose to medium produced higher values than dose to water, the differences in PTV D95% were small and range between 0 and 0.7% [17].…”
Section: Discussionmentioning
confidence: 90%
“…Differences between more advanced algorithms still exist [76][77][78][79], with Monte Carlo algorithms possibly more accurate for estimating dose at the tumour periphery [80]. There is no consensus yet about the clinical acceptability and relevance of reported differences [76,81,82]. Comparisons between 3D dose calculations using the 'average CT' dataset and full 4D calculations show small differences of a few per cent [83,84].…”
Section: Dose Calculationsmentioning
confidence: 99%
“…While this preference is clear for reference conditions of water versus soft tissue (the focus of this report), this can introduce more substantial changes in the dose reported to other media, particularly for media with very different atomic composition such as bone. Even in the lung, differences between D w,w , D w,m , and D m,m have been observed, although the magnitude of this difference varies depending on the metrics studied . These differences underscore the need for diligence if the dose reporting medium is changed, as is appropriate for any change in clinical practice.…”
Section: Discussionmentioning
confidence: 99%